Leadership Support System for the Selection of Outstanding Students Using the MAUT Method - Ahmad Hidayat; Syifa Nurani Rahmayanti; Farida Amalya (Forum Kerjasama Pendidikan Tinggi (FKPT), 2026)
A student is a person who is currently in education. Outstanding students are students who are studying or studying in higher education, both in universities, as well as institutes or academies that are being followed in order to achieve their desired goals. They are people who are prospective intellectuals who are registered as students at a college or university called students. Based on the problems that often occur, a decision support system is needed to be used in solving these problems, so every student who is continuing their education is expected to study seriously for the sake of achieving achievements according to what is desired so that in the future they will become the next generation for the nation. In this study, 7 criteria were used in the selection of outstanding students that became a reference or assessment worthy of becoming outstanding students, including activeness, certificates obtained during lectures, cumulative achievement index scores, behavior in lectures, written works, the number of parental dependents, and income. Based on the problems that often occur, a decision support system is needed to be used in solving these problems, so every student who is continuing their education is expected to study seriously for the sake of achieving achievements according to what is desired so that in the future they will become the next generation for the nation. Therefore, a decision support system is needed to solve a problem by applying the Centroid Rank Order (ROC) Method used to carry out weighting and the Multi Attribute Utility Theory (MAUT) Method which is used to solve the problem by including weighting. From the test results, the best alternative that is considered worthy as an outstanding student is in the A3 alternative for Ira using the Rank Order Centroid (ROC) Method and the Multi Attribute Utility Theory (MAUT) method with a score of 1.297.